ANALYSIS OF DYNAMIC CHARACTERISTICS OF FAULTY MAGNETIC BEARING-ROTOR SYSTEM - ZHANG LingYun; ZOU AiCheng (Jixie qiangdu)
Consider the coupling of shaft cracks, rotor eccentricity, electromagnetic force of the electromagnetic bearing, and friction force between the rotating shaft and auxiliary bearing, the Runge-Kutta method is used to obtain the electromagnetic bearing-rotor system under different fault conditions. Bifurcation diagram, maximum friction force distribution diagram, axis trajectory diagram, Poincaré mapping diagram, time response diagram, etc., specifically analyze the impact of different faults on the dynamic response of the system; identify the rub-impact phenomenon and bifurcation of the rotating shaft and auxiliary bearing Characteristics. Research shows that when a crack-rub-impact fault occurs, the system corresponds to the first-order critical speed, 1/2, 1/3 and 1/4 critical speed, and 3 times the critical speed threshold bifurcation characteristics. The change shows that the stability of the system decreases with the increase of the crack coefficient; the clearance between the rotating shaft and the auxiliary bearing has a significant impact on the dynamic characteristics of the system. When the clearance is small, the rotating shaft and the auxiliary bearing will continue to rub-impact, and the clearance After increasing, the movement of the system gradually stabilizes.